Viable sweetpotato technologies in Africa - Mozambique (VISTA). Project profile. - International Potato Center (International Potato Center, 2019)
The cultivation and consumption of sweetpotato can improve the diets and boost incomes of vulnerable families in Mozambique. To encourage more smallholders to grow sweetpotato, the project provided high quality planting material and offered training in growing, harvesting and storage methods. It also offered support in selling and marketing crops as well as training and nutrition and preparing sweetpotato.